Historical review of mixed approach to passive damper optimization for building structures under earthquake loading - Takewaki, Izuru (Frontiers in Built Environment, 2024)
Passive dampers play a key role in the smart and reliable design of building structures under uncertain earthquake loading. Passive dampers enable structural designers to enhance the potential of their structural design techniques and acquire the powerful methodologies for more reliable structures under unpredictable uncertainties. While there exist many review articles on optimization of passive dampers, this review is aimed at introducing a new perspective that most passive damper algorithms can be classified based on the combination of several component approaches with different objectives. Mixed approaches considering input uncertainties are particularly highlighted. Research focused on comparison among different optimization methods is also investigated.